Factors Influencing Adoption Of E-Wallet Function For International Transaction - Suyono Saputra; Wisnu Yuwono; Tio Sania Rachmi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research focuses on analysing the influence of factors such as Perceived Ease of Use, Perceived Usefulness, Perceived Security, Perceived Risk, and Perceiived Serviice Quality on e-wallet adoption in the context of international transactions. The sampling method used is convenience sampling, withh data collection conducted through a survey using a questionnaire distributed through the Google Form platform. The quantitative approach used in this study, with the Smart-PLS application as a tool for data processing and analysis. The results of this study are expected to provide in-depth insight into the factors that influence the use of e-wallets in carrying out international transactions.